OP0102 GENE SCREENING OF PRIMARY IMMUNODEFICIENCY DISEASES IN PATIENTS WITH JUVENILE SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - LI, J.; Wang, W.; Wang, C. Y.; Pan, J. Y.; Song, H.
Abstract : Background: Systemic lupus erythematosus (SLE) is one of the most common auto-immune diseases in childhood. Primary immunodeficiency disease (PID) patients may present or combine with autoimmune diseases. Objectives: This study aimed to perform gene sequencing via high-throughput sequencing technology in a series of Chinese pediatric SLE patients, and investigate the concomitant situation of PIDs and SLE. Gene sequencing results may help clarify the pathogenesis of SLE. Methods: This was a retrospective case series of SLE children who referred to the Peking Union Medical College Hospital between 01/2016 and 09/2019. Genetic tests were performed in patients who met the inclusion criteria. We then collected demographic, clinical, and treatment information of all involved patients. Descriptive statistics were used. Results: Seventy-one patients were finally included (eighteen boys and fifty-three girls). The median age at the time of disease onset was 9.5 (range, 3-15) years. It is notable that five patients experienced their first attack before the age of five. Twenty-seven patients showed a persistent increase in ESR during treatment, while thirteen cases presented with repeated CMV infection, thirty-four cases with persistent low complement levels, seven with basal ganglia calcification showed in skull CT or MRI, four with special type of rash (i.e., frostbite-like rash, discoid erythema, reticular erythema), two with obvious hepatosplenomegaly, and one case with type I diabetes. Gene sequencing results showed that about ten patients combine with primary immunodeficiency disease, including Aicardi-Goutières Syndrome (AGS) (n=4), Spondyloenchondro-dysplasia with immune dysregulation (SPENCDI) (n=1), STING-associated vasculopathy with onset in infancy (SAVI) (n=1), lysinuric protein intolerance (LPI) (n=1), Ras-associated autoimmune leukoproliferative disorder (RALD) (n=2). Conclusion: SLE patients who present atypical or refractory manifestations should attach importance to the existence of primary immunodeficiency disease. Genetic tests are recommended for patients with early-onset SLE, especially those with recurrent frostbite-like rash or persistent CMV infection since childhood. References: [1]T Tarr, B Dérfalvi, N Győri, et al. Similarities and differences between pediatric and adult patients with systemic lupus erythematosus[J]. Lupus. 2015, 24: 796–803. [2]Gupta S, Louis A G. Tolerance and Autoimmunity in Primary Immunodeficiency Disease: a Comprehensive Review[J]. Clinical Reviews in Allergy & Immunology, 2013, 45(2):162-169. Disclosure of Interests: None declared